Fatal case of ST8/SCCmecIVl community-associated methicillin-resistant Staphylococcus aureus infection in Japan - N. Ishitobi; T.-W. Wan; O.E. Khokhlova; L.-J. Teng; Y. Yamamori; T. Yamamoto (New Microbes and New Infections, 2018)
Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) with ST8/SCCmecIV threatens human health. However, its pathogenesis remains unclear. ST8 CA-MRSA (CA-MRSA/J) with SCCmecIVl, which carries the large LPXTG-motif–containing putative adhesin gene, spj, has emerged in Japan. We present the first reported case of death from CA-MRSA/J. The patient was a 64-year-old woman with iliopsoas abscesses complicated by septic pulmonary embolism and multiorgan abscesses. Vancomycin, arbekacin, daptomycin and rifampicin were ineffective. CA-MRSA/J was resistant to erythromycin, clindamycin and antiseptics and was invasive in a HEp-2 cell assay, in contrast to skin-derived villous-adherent CA-MRSA/J. This suggests the strongly invasive pathotype of CA-MRSA/J. Keywords: Community-associated methicillin-resistant Staphylococcus aureus, iliopsoas abscess, pathotype, septic pulmonary embolism, ST8/SCCmecIVl